2022
DOI: 10.1097/mpg.0000000000003488
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectrical Impedance Analysis (BIA)- Derived Phase Angle in Children and Adolescents: A Systematic Review

Abstract: Phase angle (PhA), a directly-measured bioelectrical impedance analysis variable, is suggested to be a proxy of body cell mass as well as extracellular/intracellular water ratio, and is related to cellular integrity and functions. The aim of this systematic review was to evaluate PhA in healthy youths in relation to sex, age, weight status, physical fitness, and sports activities. A systematic literature search (preferred reporting items for systematic reviews and meta-analyses criteria) until January 2022 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
(150 reference statements)
0
10
0
Order By: Relevance
“…Isokinetic knee flexion and extension were tested at a velocity of 60 °/s and 120 °/s using an isokinetic dynamometer (BIODEX System 4 ProTM; BIODEX, Natcon Drive Shirley, NY, USA) [ 19 ]. A bioelectrical impedance analyzer (InBody S10; Biospace, Seoul, Korea) was used to measure SMM and phase angle (PhA) [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Isokinetic knee flexion and extension were tested at a velocity of 60 °/s and 120 °/s using an isokinetic dynamometer (BIODEX System 4 ProTM; BIODEX, Natcon Drive Shirley, NY, USA) [ 19 ]. A bioelectrical impedance analyzer (InBody S10; Biospace, Seoul, Korea) was used to measure SMM and phase angle (PhA) [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…PA is not a measure of body composition per se; however, it can be considered an index of the extracellular water (ECW)/intracellular water ratio, body cellular mass, and cellular integrity in healthy and ill participants, and is directly associated with muscle strength. It varies depending on age and sex and is related to FFM 72 …”
Section: Literature Reviewmentioning
confidence: 99%
“…It varies depending on age and sex and is related to FFM. 72 Few studies have reported clinical outcomes related to body composition in sick children, especially children who are critically ill. Shime et al 73 investigated perioperative changes in BIA in 107 pediatric patients (aged 3 days to 17 years) after heart surgery and concluded that measurement of the relative changes postoperatively, which reflect perioperative alterations in body composition, provided a quantitative estimation of critical illness in these patients.…”
Section: Bioelectrical Impedancementioning
confidence: 99%
“…PhA is related to cellular functions and integrity and is suggested to be a proxy of extracellular/intracellular water ratio as well as body cell mass 5 . By definition, the PhA is directly associated to reactance and inversely associated to resistance.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 PhA is related to cellular functions and integrity and is suggested to be a proxy of extracellular/intracellular water ratio as well as body cell mass. 5 By definition, the PhA is directly associated to reactance and inversely associated to resistance. Higher PhA values appear to be consistent with greater amounts of intact skeletal muscle cell membranes and body cell mass, whereas low values suggest cell death or decreased integrity of cell membranes.…”
Section: Introductionmentioning
confidence: 99%